Fabrication and Arc Erosion Behavior of Ag-Sno2-Zno Electrical Contact Materials - Castro-Cerda, F (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study investigated the synthesis of Ag-SnO2-ZnO by powder metallurgy methods and their subsequent electrical contact behavior. The pieces of Ag-SnO2-ZnO were prepared by ball milling and hot pressing. The arc erosion behavior of the material was evaluated using homemade equipment. The microstructure and phase evolution of the materials were investigated through X-ray diffraction, energy-dispersive spectroscopy and scanning electron microscopy. The results showed that, although the mass loss of the Ag-SnO2-ZnO composite (9.08 mg) during the electrical contact test was higher than that of the commercial Ag-CdO (1.42 mg), its electrical conductivity remained constant (26.9 ± 1.5% IACS). This fact would be related to the reaction of Zn2SnO4’s formation on the material’s surface via electric arc. This reaction would play an important role in controlling the surface segregation and subsequent loss of electrical conductivity of this type of composite, thus enabling the development of a new electrical contact material to replace the non-environmentally friendly Ag-CdO composite. © 2023 by the authors.